In vitro Antioxidant and anti-inflammatory activities assessment of flavonoids crude extract of Anthemis pedunculata subsp. atlantica (Pomel) Oberpr., aerial parts. - Gaamoune, Sofiane (Algerian Journal of Biosciences, 2023)
The Anthemis genus is used in traditional medicine for treating asthma, gastrointestinal disorders, and colds, with its beneficial effects attributed to its phenolic contents. The study aims to evaluate the biological activities of this species, which is widely used by the local population by extracting of flavonoids from Anthemis pedunculata subsp. atlantica (Pomel) Oberpr. and valorised their antioxidant and anti-inflammatory potentials. The extraction process involved macerating the plant in 70% ethanol, defatting it with petroleum ether, and extracting the aqueous phase with chloroform. The flavonoid content was measured using Aluminium chloride solution, while the antiradical activity was assessed by DPPH assay. The study also evaluated the plant extract's reducing power and its ability to protect erythrocytes from membrane lysis induced by hypotonicity using the HRBC membrane stabilization method. The results show a very interesting antioxidant activity expressed by a low IC50 and EC50 in case of DPPH and reducing power test respectively. Also, the extract revealed a significant protective power of erythrocytes at a very low concentration (10−100 μg/mL).